Effects of Deficit Irrigation and Mulch on Yield and Quality of Potato Crop - Kiptoo , S.; Kipkorir , E. C; Kiptum , C. K (African Journal of Education,Science and Technology (AJEST), 2018)
Field trials were carried out at Uswo location, located in North Rift part of Kenya during March 2016-July 2016 growing seasons. The main objective was to determine the yield and quality responses of potato crop to deficit irrigation (DI) and mulch. Experimental set up was a randomized complete block design (RCBD) with three replicates. In the study, five water levels of drip irrigation (100 % ETc, 90 % ETc, 80 % ETc, 60 % ETc and 50 % ETc) with and without mulch were considered. The 100 % ETc was used as an experimental control. Deficit irrigation was carried out at different growth stages of the plant for the remaining plots. The plots were covered during a rain event with a polythene sheet as a shelter and unrolled when there was no rain. Results revealed that plots with mulches at 100 % ETc attained 50 % plant emergence earlier than those without mulches. Also highest plant heights, stems per plant and better tuber qualities were achieved in the mulched plots under 100 % ETc. Water use efficiency (WUE) increased as the irrigation water was reduced. Tuber yields ranged from 16.2±0.6 t ha-1 to 29.5±0.9 t ha-1 and 14.3±0.5 t ha-1 to 27.3±0.5 t ha-1 for mulch and non-mulch treatments respectively. WUE ranged from 33.6 to 59.8 kg/ha/mm and 30.8 kg/ha/mm to 53.4 kg/ha/mm for mulch (M) and non-mulch (NM) respectively. Optimal crop production was obtained at 80 % ETc with WUE of 40.1 kg/ha/mm and 36.9 kg/ha/mm for mulch and non-mulch respectively. Therefore optimal crop production with minimum water use is recommended for practice in farms with scarce water resources.